Prevalence of potential essential tremor cases in Turkish adolescents according to The WHIGET classification - TÜRKDOĞAN, DİLŞAD (My University, 2022)
Objective: Essential tremor is the most common movement disorder diagnosed during adolescence. However, there are insufficient data about its prevalence among adolescents. This study aims to determine the prevalence of potential essential tremor cases in Turkish adolescents. Materials and Methods: This cross-sectional study was carried out in Istanbul, Turkey. A total of 5 high schools were visited. In the first step, the authors provided 5559 students (aged 14-18) with clinical information about tremors and essential tremors in their classrooms. After that, a 12-item questionnaire filled by adolescents and parental consent forms were collected. The response rate was 78% (n = 4330). According to the questionnaire answers, adolescents who complained of experiencing tremors in any part of their body were clinically evaluated in the second step of the study. Lastly, a neurological examination to classify essential tremors based on the Washington Heights Inwood Genetic Study of Essential Tremor (1998) diagnostic criteria was conducted by a specialist. Results: The prevalence of tremor in the respondents aged 14-18 (median = 15) years was 1.2 % (n = 52/4330), and the prevalence of essential tremor was 0.41% (n = 18/4330). Male to female ratio for essential tremor was 5 : 1 (male = 15 and female = 1). Essential tremor cases were subclassified as following: 10 (55.5%) definite essential tremor, 3 (16.6%) probable essential tremor, and 5 (27.7%) possible essential tremor. Conclusion: The data support the claim that essential tremor is a prevalent movement disorder in Turkish adolescents.
Keywords: Tıp; Sağlık Bilimleri; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Medicine; Health Sciences; Internal Medicine Sciences; Child Health and Diseases; PEDİATRİ; Klinik Tıp; Klinik Tıp (MED); PEDIATRICS; CLINICAL MEDICINE; Clinical Medicine (MED); Pediatri; Pediatri, Perinatoloji ve Çocuk Sağlığı; Pediatrics; Pediatrics, Perinatology and Child Health; Prevalence; tremor; essential tremor; adolescents; MOVEMENT-DISORDERS; CHILDHOOD; GENETICS; GENDER; Prevalence; tremor; essential tremor; adolescents